Damages for Indirect Patent Infringement - Dmitry Karshtedt (Washington University Law Review, 2014)
In many patent infringement cases, the only practical way that the plaintiff can obtain relief is on a theory of secondary liability, which is generally referred to as indirect infringement. The remedy in patent cases frequently includes damages for past infringement. Because jury verdicts in patent cases can amount to hundreds of millions of dollars, patent damages have become a hotly litigated issue. Nevertheless, much to the frustration of the litigants in these high-stakes lawsuits, the courts continue to struggle to clarify how damages for indirect infringement should be determined. The Court of Appeals for the Federal Circuit, which has exclusive appellate jurisdiction over patent cases, has deepened the confusion over calculating damages. Two opinions from the Federal Circuit have made contradictory pronouncements on the issue of accounting for proven acts of primary (i.e., direct) infringement in determining damages for indirect infringement. Lucent Technologies, Inc. v. Gateway, Inc. held that the extent of directly infringing use of the patent should be viewed as one of many pieces of evidence for measuring the extent of damages (“the evidentiary approach”). In contrast, Cardiac Pacemakers, Inc. v. St. Jude Medical, Inc. endorsed a rule that enables trial judges to limit damages as a matter of law to proven, enumerated acts of direct infringement of the asserted patents (“the atomistic approach”). The conflict between the two approaches raises fundamental, unanswered questions concerning the relationship between patent infringement and ordinary torts. This Article fills a gap in the literature by identifying, and working toward unraveling, one of the puzzles of indirect infringement. Specifically, it examines what the legal fiction of formally imputing an act of one entity to another—an important tenet of secondary liability in tort—means for patent damages. The answer is surprising: the atomistic approach is consistent with the principles of tort law, but is at odds with well-established, general rules for determining patent damages. Conversely, the evidentiary approach seems to ignore tort law’s imputation principle and embodies the pragmatic, patent-specific damages rules that the atomistic approach eschews. This Article resolves the tension in favor of the evidentiary approach and explains that considerations of policy, logic, and precedent support a damages analysis that reflects fundamental differences between patent law and tort law.
Keywords: patent infringement; secondary liability; indirect infringement; remedy; damages; Federal Circuit; Lucent Technologies; Inc. v. Gateway; Inc.; Cardiac Pacemakers; Inc. v. St. Jude Medical; evidentiary; pragmatic; tort